Clinical justification of the use of a three-part two-support bridge prosthesis - I. O. Buentsov; A. M. Nesterov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Describes the relevance of the use of fixed orthopedic structures in prosthetics of patients with partial absence of teeth. Clinical features of orthopedic rehabilitation of a patient with this pathology are revealed. The results of a computational experiment on choosing the optimal sizes of the supporting parts of a three-part bridge prosthesis are presented. The technology of manufacturing a bridge prosthesis is described and the nearest clinical results of treatment of this disease are given.